Modular System Design of Jajar Legowo Rice Transplanter Machine - Athoillah Azadi; Tineke Mandang; Wawan Hermawan; Mardison Mardison (The University of Lampung, 2025)
The Jajar Legowo rice transplanter has been proven to significantly improve the efficiency and effectiveness of rice planting, delivering better quality and uniformity. However, mobility on terraced land remains the primary challenge, thereby hindering the adoption of this technology by farmers. This study aimed to redesign the jajar legowo rice transplanter into a modular system to improve adaptability and ease of transport in such terrains. The research consisted of two main stages: module determination which included functional analysis, weight assessment, and component interconnection evaluation, while design analysis employed Finite Element Analysis (FEA) to assess structural strength and reliability through stress simulation. The findings indicated four main modules for the transplanter, namely: main transmission module, wheel module, feeding transmission module, and floating module. The module components have a maximum weight of 62.9 kg, which can be feasibly transported by two operators. The transmission neck interface and wheel transmission sustained operational loads of 700 N and 1000 N, respectively, with corresponding safety factors of 1.7 and 1.9. This study successfully developed a modular design for the jajar legowo rice transplanter machine that can be effectively used on terraced field. The design meets three critical adaptability indicators: (1) module weights remain within the lifting capacity of a maximum of two operators, (2) sufficient structural strength is maintained to endure operational loads, and (3) the assembly and disassembly process is achieved without the need for additional tools, minimizing the risk of component loss in the field. Keywords: Interface, Jajar legowo, Module, Rice transplanter, Stress analysis.